Math, asked by shraksha5, 3 months ago

-7×-7×-7×-7 in exponential form​

Answers

Answered by parthivanil2002
0

Answer:

7^4

(-7)^4=(-1)^4×(7)^4

-1 raised to even number is 1

so 1× 7^4=7^4

Answered by TrustedAnswerer19
39

\huge\mathbb\color{purple}{AN}\purple{SW}\pink{ER}\color{pink}{:}

Method - 1:

( - 7) \times ( - 7) \times ( - 7) \times ( - 7) \\  = ( - 1) \times ( -1 ) \times 7 \times 7 \times ( - 7) \times (  - 7)  \\ = 1 \times 7 \times 7 \times ( -1 ) \times ( -1 ) \times 7 \times 7  \\ = 7 \times 7  \times 1\times 7 \times 7 \\  =  {7}^{4}

Note :

( - ) \times ( - ) = ( + ) \\ ( - ) \times ( + ) = ( - )

Method -2 :

( - 7) \times ( - 7) \times ( - 7) \times ( - 7) \\  = ( -1 ) \times ( -1 ) \times ( - 1) \times ( - 1) \times 7 \times 7 \times 7 \times 7 \\  =  {( - 1)}^{4}  \times  {7}^{4}  \\  = 1 \times  {7}^{4}  \\  =  {7}^{4}

Note :

 {( - 1)}^{n}  \\  = 1 \:  \:  \: when \:  \:  \: n \:  = even \\ =   - 1 \:  \:  \: when \:  \:  \: n \:  =  \: odd

Similar questions